Aspectos que conferem complexidade a interpretação na perspectiva do intérprete educacional do ensino médio - Oliveira, Patricia Cardoso de (2023)
At the expense of a greater insertion of the deaf in the academic environment, the educational intérpreter of Brazilian Sign Language - Libras, has been gaining recognition in relation to the importance of its performance and its influence in the teaching and learning process of students with deafness. That said, the present study explored the aspects that add complexity to the interpretation of Portuguese into Libras in the educational environment, aiming to identify, understand and offer reflections on the elements that foster this phenomenon, with the aim of building new perspectives in the field of action of the educational intérpreter Libras, with emphasis on collaborative work between the teacher and the educational intérpreter. For this, a single case study was carried out, using the simple self-confrontation instrument, proposed by Yves Clot (2010), in work psychology (Clinic da Atividade) and based on the principles of Bakhtin's dialectic (2006), together with the conception of “Saying the 'same' to others: essays on translation” by Adail Sobral (2008), as well as the theorization about the work in partnership between the teacher and the educational intérpreter. For the analyses, two categories were highlighted: i) constructions of new concepts or complex concepts in the source discourse; and ii) interpretive lapses. Such categories provided the survey of elements that confer complexity to the interpretative act in the educational sphere, which were organized in the following axes: I) Construction of concepts: from simple to complex; II) the collaborative work between the teacher and the educational intérpreter; III) emotional aspects in the performance of the educational intérpreter. The highlighted elements, which according to the perspective of the high school educational intérpreter, exert great influence in making the task of interpreting from Portuguese into Libras usually complex, if better known they can be tackled in the perspective of making the work of the educational intérpreter of Libras less arduous.